1995
DOI: 10.1002/mrd.1080400116
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and meiotic maturation of the mammalian oocyte

Abstract: The role of calcium in the regulation of both the meiotic and mitotic cell cycles has been the subject of considerable investigation in the nonmammalian field. In contrast, the mechanisms for signalling meiotic maturation in the mammalian oocyte are not as well documented nor as clearly defined. In the mammalian oocyte, calcium is associated with both spontaneous and hormone-induced meiotic maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 129 publications
(198 reference statements)
1
74
0
3
Order By: Relevance
“…The hypothesis of a possible involvement of CASR in oocyte maturation is supported by several studies reporting the Ca 2C ion as a fundamental messenger for oocyte maturation (Homa 1995, He et al 1997. The rise in cytosolic Ca 2C in immature oocytes (germinal vesicle (GV) stage) following LH and/or growth factor exposure is well known (Mattioli et al 1998, Hill et al 1999.…”
Section: Introductionmentioning
confidence: 93%
“…The hypothesis of a possible involvement of CASR in oocyte maturation is supported by several studies reporting the Ca 2C ion as a fundamental messenger for oocyte maturation (Homa 1995, He et al 1997. The rise in cytosolic Ca 2C in immature oocytes (germinal vesicle (GV) stage) following LH and/or growth factor exposure is well known (Mattioli et al 1998, Hill et al 1999.…”
Section: Introductionmentioning
confidence: 93%
“…To date, little information is available on the function of this ion during oocyte maturation; however, an integral attribute of oocyte maturation is the remodeling of calcium signaling pathways endowing the oocyte with the capacity to produce a specialized calcium transient at fertilization [Homa 1995;Carroll et al 1996;Machaca 2007;Boni et al 2007]. Recent studies have shown that cytoplasmic maturation is also accompanied by a modification of plasma membrane permeability due to ion currents flowing through ion channels located on the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…This results in GVBD. The presence of low frequency spontaneous calcium oscillations, generated perhaps as a consequence of a n autonomous program, may be sufficient to activate some of the cyclins required for the transition from G, stage to metaphase (G,/M) at a relatively early stage of development (Homa, 1995). The resumption of meiotic maturation of mammalian oocyte is regulated by intracellular free calcium.…”
Section: Resultsmentioning
confidence: 99%
“…Studies concerning the effects of extracellular calcium on resumption of meiosis have been carried out using calcium deficient media, calcium chelators, calcium channel blockers a n d calcium ionophores (Homa, 1995). However, evidence for the role of extracellular calcium on GVBD remains contradictory.…”
Section: Resultsmentioning
confidence: 99%